Email Communication Styles across Cultures - Holtbrügge, Dirk; Berning, Sue Claire (The International Encyclopedia of Intercultural Communication, 2017)
Email communication is recognized as the most often used communication method in international companies' operations. This computer‐mediated communication technology constitutes a further layer of intercultural communication in the global workplace. Variations in email communication styles exist due to cultural differences and can be explained by E. T. Hall's dimensions of context, time, and space orientation. Particularly, cultural background has a significant impact on the preference for formalness, promptness, preciseness, task orientation, and relationship‐relatedness in email communicati
Keywords: Intercultural Communication